Effect of iron and bismuth addition on the microstructure and mechanical properties of sac105 solder under severe thermal environment / Bakhtiar Ali - Bakhtiar, Ali (2017)
The transition to lead-free soldering for the electronic industry has been necessitated by the health and environmental concerns over the usage of lead and lead-containing products. Many lead-free solders have been extensively researched for this purpose. Amongst all, the near-eutectic Sn-3.0Ag-0.5Cu (SAC305) and Sn-4.0Ag-0.5Cu (SAC405) solders were termed as the most suitable replacements for lead-tin (Sn-Pb) solder, particularly in surface mount technology (SMT), owing to the excellent electrical and thermal properties of Ag and Cu. However, due to their low reliability during high strain rate exposures, like drop and shock and the high cost of Ag, various SAC solder alloys with lower-Ag-content have been suggested, including 98.5Sn-1.0Ag-0.5Cu (SAC105). Nevertheless, their low mechanical performance as well as low stability during thermal exposures limit their range of applications. A limited number of studies have indicated that the addition of alloying elements to the low-Ag-content SAC solders can improve their mechanical properties as well as stabilize their properties under high temperature exposures. This work aims to investigate the effect of iron (Fe) and bismuth (Bi) addition on the microstructural and mechanical properties of Sn-1Ag-0.5Cu (SAC105) solder alloy under severe thermal exposures. The isothermal aging was done at 200 °C for 100 h, 200 h, and 300 h. The average grain size significantly reduced with Fe/Bi addition to the base alloy Sn-1Ag-0.5Cu and remained literally the same after thermal aging. Fe/Bi added Sn-1Ag-0.5Cu showed a significant reduction in the IMCs size (Ag3Sn and Cu6Sn5), especially the Cu6Sn5 IMCs and a refinement in the microstructure, which is due to the presence of Bi in the alloys. Moreover, their microstructure remained much more stable under severe thermal aging conditions, which is due to the presence of both Fe and Bi in the alloy. The tensile testing results showed that Fe/Bi addition to Sn-1Ag-0.5Cu significantly improved the tensile properties. Likewise, the impact absorbed energy increased by about 20% with the 0.05 wt.% Fe and 1 wt.% Bi addition to the Sn-1Ag-0.5Cu alloy and literally no further improvement was observed by increasing the Bi content in the alloy. The addition of Fe/Bi to Sn-1Ag-0.5Cu increased the hardness of the alloy by more than two fold. Shear strength almost doubled for the Fe/Bi added Sn-1Ag-0.5Cu, as compared to the base alloy. Improvements in these mechanical properties is due to the Bi solid solution strengthening mechanism. Under severe thermal aging, the Fe/Bi added Sn-1Ag-0.5Cu showed more stable mechanical properties than the base alloy, owing to the presence of both Fe and Bi in the alloys. The Fe/Bi added Sn-1Ag-0.5Cu solder alloys showed a potential for the severe thermal environments’ applications of as high as 200 °C, along with low cost and much improved microstructure and mechanical properties.